Kilometer-Scale Sound Speed Structure That Affects GNSS-A Observation: Case Study off the Kii Channel - Yokota, Yusuke; Ishikawa, Tadashi; Watanabe, Shun-ichi; Nakamura, Yuto (Frontiers in Earth Science, 2020)
The Global Navigation Satellite System-Acoustic ranging combination technique (GNSS-A) is a recently developed technology to precisely detect seafloor crustal deformation. This method can also estimate km-scale underwater sound speed structure (SSS) as a by-product of monitoring seafloor crustal deformation. This paper evaluates the validity of the spatial gradient and its temporal variation of the SSS estimated by GNSS-A observations off the Kii channel before and after Kuroshio meandering. According to the comparison of the JCOPE2M reanalysis data and the in-situ observation data, the GNSS-A estimated SSS has local structures that are not reproduced in this reanalysis but were detected by in-situ data. In addition, we investigate the effect of observation time on the stability of SSS estimation. The results suggest that the sufficient time required for stable estimation depends on the spatial coverage of observation data, which depends on the depth of the site. As a result, the time resolution was derived to be about one hour at a site whose depth is 1500 m.